SDF1α‐induced interaction of the adapter proteins Nck and HS1 facilitates actin polymerization and migration in T cells. Issue 2 (28th November 2014) - Lettau, Marcus; Kabelitz, Dieter; Janssen, Ottmar
<x xml:space="preserve">Abstract</x> Noncatalytic region of tyrosine kinase (Nck) is an adapter protein that comprises one SH2 (Src homology) domain and three SH3 domains. Nck links receptors and receptor‐associated tyrosine kinases or adapter proteins to proteins that regulate the actin cytoskeleton. Whereas the SH2 domain binds to phosphorylated receptors or associated phosphoproteins, individual interactions of the SH3 domains with proline‐based recognition motifs result in the formation of larger protein complexes. In T cells, changes in cell polarity and morphology during T‐cell activation and effector function require the T‐cell receptor‐mediated recruitment and activation of actin‐regulatory proteins to initiate cytoskeletal reorganization at the immunological synapse. We previously identified the adapter protein HS1 as a putative Nck‐interacting protein. We now demonstrate that the SH2 domain of Nck specifically interacts with HS1 upon phosphorylation of its tyrosine residue 378. We report that in human T cells, ligation of the chemokine receptor CXCR4 by stromal cell‐derived factor 1α (SDF1α) induces a rapid and transient phosphorylation of tyrosine 378 of HS1 resulting in an increased association with Nck. Consequently, siRNA‐mediated downregulation of HS1 and/or Nck impairs SDF1α‐induced actin polymerization and T‐cell migration.